STELLARIUM SOFTWARE ENVIRONMENTAS A MEANS OF DEVELOPING RESEARCH COMPETENCE OF HIGHER EDUCATION STUDENTS - MOKHUN, Serhii; FEDCHYSHYN, Olha; HOROSHKEVYCH, Oleksandr; SITARSKYI, Bohdan (Physical and Mathematical Education, 2024)
Formulation of the problem. The modern education system is only possible with the active use of information and digital technologies, online services, and platforms. Reforming physical and astronomical education content is only possible by considering the theoretical and methodological foundations for developing students’ research competence. Therefore, specialized software environments such as Stellarium are used in educational activities to implement a competency-based approach, particularly to form research competence. For educational purposes, Stellarium is used to form ideas about the apparent annual motion of the Sun and the movements of the planets, to determine distances to celestial objects, as interactive multimedia to understand and motivate students in astronomy, etc. Given that one of the most critical tasks of modern astronomy is the study of exoplanets, the authors describe the methodology for studying the TOI 700 planetary system. Materials and methods. To clarify the state of research on the problem in pedagogical theory and practice, we follow the theoretical techniques of analysis, comparison, systematization, and generalization of educational, scientific, and applied sources and electronic resources on the research problem. Results. The article considers the didactic and methodological possibilities of the virtual planetarium Stellarium for forming students’ research skills and abilities in studying exoplanets. The study proposes implementing the practical task "Study of the TOI 700 planetary system" to develop students’ research skills. Conclusions. Educational process subjects can use the proposed algorithm to study exoplanets as didactic material for creative and individual academic and research tasks. The use of information and digital technologies ensures the development and activation of students’ cognitive interests, the formation of research skills, the possibility of self-study, and the ability to critically analyze the results of their activities.